Properties of Concrete Subjected to Extreme Thermal Conditions. (1st March 2014) - Bamonte, Patrick; Gambarova, Pietro
Abstract : Durability, high-temperature resistance, impact and blast resilience, radiation-shielding properties, irradiation endurance and - of course - good mechanical properties are required of the cementitious composites to be used in a variety of high-performance structures. Among these, tall buildings, road and railway tunnels, off-shore platforms, gasification plants, wind and solar mills for the production of "clean" energy should be mentioned, as well as nuclear power plants, and radioactive- and hazardous-waste repositories. Hence, understanding, measuring and modelling concrete behavior under extreme environmental conditions is instrumental in making concrete structures safer and more efficient. To this end, the hot and residual properties associated with the exposure to high temperature, fire and thermal shock are treated in this paper. Reference is made to ordinary vibrated concrete (Normal-Strength Concrete - NSC), as well as to a number of innovative cementitious composites, such as Fiber-Reinforced Concrete - FRC, High-Performance/High-Strength Concrete - HPC/HSC, Ultra High-Performance/Very High-Strength Concrete - UHPC /VHSC, Self-Compacting/Consolidating Concrete - SCC, Light-Weight Concrete - LWC, shotcrete and high-strength mortars. It is shown that these materials can be "tailored" according to a variety of requirements and functions, even if several aspects of their behavior (like spalling in fire and long-term mechanical properties under sustained high temperature) are still open to investigation.